Sams teach yourself Android application development in 24 hours - Darcey, Lauren, 1977- (Sams teach yourself., 2012)
Android is the world's #1 mobile development platform, and with the new Android 3.0, it's becoming as popular for tablets as it is for smartphones. If you are a beginner, in just 24 lessons of one hour or less, this friendly, full-color book will help you master modern Android development. You can build a fully-featured app from scratch, learning all the skills you'll need to create your own. Each lesson builds on prior chapters, providing a solid foundation for success. This edition is thoroughly updated for Android's newest features and development tools, while still supporting the popular Android 2.0. Coverage includes: Using Eclipse to write apps quickly and efficiently Understanding the application lifecycle Building robust, friendly user interfaces Retrieving, storing, and using data Adding network, social, and location-based features Supporting the camera and other hardware Internationalizing, testing, and publishing apps Revised and simplified step-by-step instructions with full-color screenshots walk you through key tasks ... updated Q and As, Quizzes, and Exercises test your knowledge ... "Did You Know?" tips offer insider advice ... "Watch Out!" alerts help you avoid problems. By the time you're finished, you won't just understand core Android concepts: you'll be comfortable writing, testing, and publishing your own new apps.